Role of limonin in anticancer effects of Evodia rutaecarpa on ovarian cancer cells - Jae Ryul Bae; Wook Ha Park; Dong Hoon Suh; Jae Hong No; Yong Beom Kim; Kidong Kim (BMC, 2020)
Abstract Background Ovarian cancer therapy generally involves systemic chemotherapy with anticancer drugs; however, chemotherapy with a platinum-based drug has often been shown to cause adverse reactions and drug resistance in ovarian cancer patients. Evodia rutaecarpa (ER) reportedly shows anticancer activity against various types of cancer cells. However, the effects of ER have not yet been fully uncovered in ovarian cancer. Methods In the present study, we investigated the anticancer effects of an ER extract and its components against the ovarian cancer cell lines SKOV-33, A2780, RMUG-S and a cisplatin-resistant SKOV-3 cell line (CisR SKOV-3). Cell viability and colony formation assays along with subcellular fractionation analysis, immunoblotting, and immunofluorescence staining were performed. Results ER treatment led to a significant reduction in the viability of SKOV-3 cells. Moreover, limonin, a compound found in ER, reduced the viability of both serous-type (SKOV-3 and A2780) and mucinous-type (RMUG-S) ovarian cancer cells by inducing apoptosis via activation of the p53 signaling pathway. Furthermore, limonin reversed the drug resistance through activation of apoptosis in CisR SKOV-3. Conclusion Taken together, our findings suggest that limonin contributes to the anti-ovarian cancer effects of ER by inducing apoptosis via activation of the p53 signaling pathway.